Franchising in the region. - Cheong, Yin May. (2013)
Franchising involves a contractual arrangement between the owner (franchisor) of a business and an entrepreneur (franchisee), which allows the franchisee to conduct business in a prescribed manner over a specific period of time using the business trademarks, products, services and business systems developed by the franchisor. Franchising in Singapore has seen substantial growth in recent years and home-grown franchisors have also made considerable inroads into the regional markets. This prompts us to conduct a study to explore franchising further. The purpose of the study is to establish the extent to which franchising provides an easier and quicker route to regional business expansion. We also hope to identify the characteristics and success factors of enterprising home-grown franchisors who have ventured into the region. Local franchisors who have yet to regionalise will also be studied. A comparison between these two groups of franchisors is then carried out. This study covers the background of the franchise industry and the concepts of franchising in Chapter 2. The role played by the Singapore government in aiding franchisors expand into the region is also explored in the same chapter. Chapter 3 presents the research methodology, while chapter 4 and 5 present the case studies on local franchisors who have not regionalised and those who have. Our last chapter concludes the study and recommendations are made. We conclude that franchising is a quicker but not necessarily an easier route to business expansion. We also recommend potential franchisors to conduct market research, establish in Singapore first, be willing to commit, carefully select the right franchisees, guard one’s proprietary advantage and seek assistance from the government before going into franchising.